Analisis Daya Saing Terminal Kendaraan Domestik Berbasis Pada Kinerja Logistik Dan Strategi Pemasaran Di Pelabuhan Patimban - Herdian, Tedy; Ferdiansyah, Anton; Ponto, Karen Nevia Abigail; Puspita, Sesaria Mardhiani Rachma; Bijaksana, Gena; Sholihah, Sita Aniisah (Jurnal Sistem Transportasi & Logistik, 2022)
Domestic CBU flows at Car Terminal of Tanjung Priok Port are increasing. This resulting in a decrease of utilization in the open field at domestic car terminals. This can lead to excessive cost increases and also cause congestion in the Tanjung Priok Port area. Therefore, the Car Terminal at Patimban Port was built with the aim of reducing logistics costs caused by congestion at Tanjung Priok Port. This study aims to describe the competitiveness based on logistics performance and the right marketing strategy to be applied at the Domestic Car Terminal of Patimban Port in 2021.The research method used is descriptive qualitative with an approach using Resource Based View (RBV) analysis, Politic, Economics, Social, Technology, Legal,and Environment Analysis PESTLE analysis and Five Forces Porter Model Analysis. Furthermore, to determine the strengths, weaknesses, opportunities and threats of the Domestic Car Terminal at Patimban Port SWOT analysis and also 7 P's Marketing Mix was used to determine the right marketing strategy. The results of this study reveal that The Domestic Car Terminal of Patimban Port doesn’t have competitiveness yet according to Porter Competitiveness indicator. Therefore, marketing strategy has been identified and developed for the sustainable of Domestik Car Terminal business in Patimban Port. In terms of logistics performance, the Domestic Car Terminal facility is one of the strength factors for the Domestic Car Terminal of Patimban Port.